1961
DOI: 10.1136/sti.37.2.145
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of N. Gonorrhoeae to Antibiotics

Abstract: Since the late thirties, physicians have been in a very fortunate position with regard to the therapy of gonorrhoea. At that time the sulphonamide drugs were discovered and produced a revolution in the treatment of gonorrhoea; when the incidence of resistant gonococcus strains became too high, penicillin came into the picture, closely followed by streptomycin and tetracycline. In addition, other antibiotics have a considerable effect on the gonococcus in vivo and in vitro (chloromycetin, erythromycin, oleandom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0
2

Year Published

1973
1973
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 7 publications
1
17
0
2
Order By: Relevance
“…Remarkably small doses (e.g., 100,000 units altogether) were used to cure gonorrhoea (Mahoney et al 1945), an occurrence reflecting the high susceptibility of the gonococcus to penicillin (Reyn et al 1958). During the subsequent decades a gradual increase in gonococcal resistance to penicillin, documented in the United States (Martin et al 1970) and elsewhere (Amies 1969, Reyn 1961, Arya & Phillips 1979, needed increases in the dose of penicillin as well as the addition of probenecid to maintain effective therapy (Holmes et al 1973, Kaufman et al 1976). In the United States, however, a reduction in gonococcal resistance to penicillin has been witnessed since 1972 (Reynolds et al 1976), and in 1976 a substantial decline in the rate of increase in morbidity from gonorrhoea was observed (CDC 1977).…”
mentioning
confidence: 99%
“…Remarkably small doses (e.g., 100,000 units altogether) were used to cure gonorrhoea (Mahoney et al 1945), an occurrence reflecting the high susceptibility of the gonococcus to penicillin (Reyn et al 1958). During the subsequent decades a gradual increase in gonococcal resistance to penicillin, documented in the United States (Martin et al 1970) and elsewhere (Amies 1969, Reyn 1961, Arya & Phillips 1979, needed increases in the dose of penicillin as well as the addition of probenecid to maintain effective therapy (Holmes et al 1973, Kaufman et al 1976). In the United States, however, a reduction in gonococcal resistance to penicillin has been witnessed since 1972 (Reynolds et al 1976), and in 1976 a substantial decline in the rate of increase in morbidity from gonorrhoea was observed (CDC 1977).…”
mentioning
confidence: 99%
“…In 1961, Reyn reported that gonoccal isolates resistant to penicillin were likely to be resistant to tetracycline and streptomycin (8). Since then, other workers have found that gonococcal isolates resistant to penicillin also tended to be resistant to erythromycin (10), chloramphenicol (1), fusidic acid (10), and rifampin (7), as well as some nonantibiotics, acridine orange and ethidium bromide (6).…”
mentioning
confidence: 99%
“…Although erythromycin and azithromycin, in the 1-g dose, are not recommended for treatment of gonococcal infection, azithromycin has been used in some parts of the world to treat gonorrhea (7,30). Increased gonococcal resistance to erythromycin has been noted since the 1960s (19), and resistance to azithromycin has been recently identified (7,13). Gonococcal resistance to erythromycin has been linked to resistance to killing by fecal lipids, and such resistant strains are more likely to be recovered from men who have sex with men than from heterosexual men (9).…”
mentioning
confidence: 99%